2018
DOI: 10.1177/1940082918788450
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Period, Behavior Development, and Growth Pattern of a Newborn Formosan Pangolin (Manis pentadactyla pentadactyla) in the Wild

Abstract: The Formosan pangolin mainly inhabits the lowland forest in Taiwan. Biological information on pangolins is limited due to their solitary behavior. This study reports the first field record of the behavior development and growth pattern of a newborn male Formosan pangolin during the entire nursing period in the wild. The methods used in this study were radio-tagging and camera-trapping. Data collection for this study was conducted from November 2014 until May 2015. The nursing period was 157 days. The infant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 6 publications
3
15
0
Order By: Relevance
“…Subadults are especially vulnerable to injury during the summer months from May to August (Fig 2), as the weaning period ends and maternal care stops [21]. This pattern is also consistent with previously reported rehabilitation records [10].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Subadults are especially vulnerable to injury during the summer months from May to August (Fig 2), as the weaning period ends and maternal care stops [21]. This pattern is also consistent with previously reported rehabilitation records [10].…”
Section: Discussionsupporting
confidence: 88%
“…Females were classified as subadults if they weighed between 1.5kg and 3kg, while females weighing more than 3kg were classified as adults. Based on long-term monitoring of radio-tagged individuals and their offspring in the study area [20], Taiwanese pangolins become independent at about 6 months [21], weighing approximately 1.5kg when they leave their mother, and reach their adult body weight at about 3 years old.…”
Section: Methodsmentioning
confidence: 99%
“…The winding passageway of the burrow ensures that the nest room in the burrow will not be flooded in the event of heavy rain [89,90] . In Taiwan, Sun et al (2018) found that when pangolins stay inside a burrow, the hole is usually blocked with mud, leaving only a small gap at the top of the wall to allow air to circulate [91] . The researchers speculate that this is a way for pangolins to protect themselves from predators, such as the reticulated python (Python reticulatus), which preys on Sunda pangolin (Manis javanica) [92] , while they are inside the burrow.…”
Section: Burrows Providing Shelter and Thermal Refugia For Commensal Animalsmentioning
confidence: 99%
“…Due to their sensitive nature and special feeding habits, they tend to be stressed and refuse to eat artificially prepared food under captivity. Veterinary research centers in Taiwan, Hong Kong, mainland China, and Vietnam have found that captive pangolins are likely to develop stomach ulcers and gastrointestinal bleeding and often die within 100 days of being raised [28,29]. In the past 20 years, Taiwan has gained considerable experience and made great achievements in the rescue and breeding of pangolins.…”
Section: Literature Reviewmentioning
confidence: 99%